Targetable GOPC-ROS1 Gene Fusion Identified in a Case of Lethal Oral Mucosal Melanoma. (21st September 2018) - East, Ellen; Plouffe, Komal; Harms, Kelly; Patel, Rajiv; McHugh, Jonathan; Tomlins, Scott; Udager, Aaron
Abstract: Oral mucosal melanoma (OMM) is an aggressive and uncommon subtype of melanoma, comprising less than 1% of all melanomas in the United States. Little is known about its molecular underpinnings, although recent data suggest a molecular profile distinct from its cutaneous counterparts. Herein, we describe a case of lethal OMM with a novel targetable ROS1 gene fusion identified by integrative targeted molecular profiling. Case Report: A 60-year-old man presented with a 1-month history of an ulcer of the posterior maxillary tuberosity. Biopsy and subsequent maxillectomy demonstrated ulcerated invasive mucosal melanoma. Despite adjuvant radiation therapy, 5-month postoperative imaging revealed metastatic progression. To identify potential targetable therapeutic options for chemotherapy, targeted next-generation DNA sequencing (DNAseq) was performed and was negative for hotspot mutations in BRAF, CTNNB1, GNA11, GNAQ, KIT, MAP2K1, and NRAS. The patient's health rapidly deteriorated, and he died 7 months following diagnosis. Given the lethal course of this patient's OMM and lack of identified targetable therapeutic alterations, targeted molecular profiling was performed posthumously on tumor tissue using targeted next-generation DNAseq and RNA sequencing (RNAseq). Targeted RNAseq identified a highly expressed GOPC-ROS1 gene fusion transcript, uniting GOPC exons 1 to 4 to ROS1 exons 5 to 12. Targeted DNAseq demonstrated two-copy loss of CDKN2A and chromosome 8 gain without prioritized somatic variants. Conclusion: Here, we describe a case of OMM with a novel GOPC-ROS1 gene fusion. Tyrosine kinase inhibitors, including crizotinib and entrectinib, have demonstrated activity against ROS1-associated signaling pathways and are used to treat advanced carcinomas with ROS1 gene fusions. A recent report described a patient with metastatic acral lentiginous melanoma harboring a GOPC-ROS1 gene fusion that showed a durable response to entrectinib therapy. Thus, patients with aggressive noncutaneous head and neck mucosal melanoma may benefit from comprehensive molecular profiling beyond the canonical melanoma-associated oncogenic mutations, in order to identify potential novel targetable molecular alterations.